Quality of Services provided by the nucleus of transport of a federal higher education institution (Research, Society and Development, 2020)
This study sought, through the adaptation and application of an evaluation instrument, to conduct a survey with users of the transport sector of a federal institution of higher education and, consequently, to verify in which dimensions of quality and in which aspects the sector should improve. Therefore, the general objective of the work was to identify the users' perception in relation to the quality of the services provided. Thus, this study was presented as a case study and was classified as a research of a descriptive nature with a quantitative methodological approach. As a research instrument, a questionnaire was used, based on the SERVPERF and QUALBUS scales. A total of 512 questionnaires were collected. The main results reveal that both the positive and negative points of the users' evaluation referred, especially, to the factors "Reliability and Safety in travel" and "Empathy in travel". Differences in assessment were also analyzed according to the profile of users, with six variables showing differences in mean: type of link, length of institution, management position, type of use of transportation, level of difficulty in scheduling and transportation from another institution. Several propositions were also made about the factors/categories surveyed, among which the following stand out: implementing a computerized system for scheduling transportation, investing in the training and professionalization of the secretariat and drivers, improving the mechanical conditions of vehicles and conducting research on travel satisfaction/assessment.